Aplikasi Pendeteksian Bentuk Gestur Tangan Dalam Bahasa Isyarat: Hand Gesture Detection Application in Sign Language - JUAN MEDELLU; Alwin Sambul; Arie S.M. Lumenta (Jurnal Teknik Informatika, 2022)
Abstract — The communicant is a liaison between 2 things aiming to be able to understand each other. Communication is very closely related to living creatures such as humans who are always social which can be interpreted a little as humans who want to convey something to other humans. With the application of technology such as a hand gesture pattern detection system, it can make it easier to recognize sign language by implementing a framework such as Yolo to detect the shape of hand signals in sign language in the form of letters being exhibited. Key words— Deep Learning, Training, Dataset, Hand Gestures, Sign Language, Framework Yolo Abstrak — Komunikan merupakan sebuah penghubung antara 2 hal bertujuan untuk dapat mengerti satu sama lain. Komunika sangat erat hubungannya dengan makluk hidup seperti manusia yang selalu bersosial dimana dapat sedikit diartikan sebagai manusia yang ingin menyampaikan suatu hal pada manusia lain. Dengan adanya penerapan teknologi seperti system pendeteksi pola gestur isyarat tangan dapat memudahkan untuk mengenal Bahasa isyarat dengan mengimplementasikan framework seperti yolo untuk medeteksi bentuk isyarat tangan dalam bahasa isyarat berupa huruf yang sedang diperagakan. Kata kunci — Pembelajaran Mendalam, Pelatihan, Himpunan Data, Gestur Tangan, Bahasa Iyarat, Kerangka Yolo.